Development Planning and Community Participation in Development Planning Consultations in the Economic Sector the Regional Development Planning Agency (BAPPEDA) Nabire District 2019-2021 - Syafiuddin, Eddy Lukman; Mulyawan, Rahman; Yuningsih, Neneng Yani (Budapest International Research and Critics University, 2022)
The purpose of this study (1) To analyze the development planning process in the Economic Sector of the Regional Development Planning Agency (Bappeda) of Nabire Regency for 2019-2021; (2) To analyze community participation in the Development Planning Deliberation in the Economic Sector, the Regional Development Planning Agency (Bappeda) of Nabire Regency in 2019-2021. The research uses a qualitative approach through the process of finding, understanding, explaining and obtaining an overview. ResultThe development planning process for the Economic Sector of the Nabire Regency Bappeda for 2019-2021 is carried out with a bootom-up approach, starting from the village-level Musrenbang, followed by the district-level Musrenbang and District, Provincial and National levels. The level of proposed activity programs proposed at the planning stage is quite high, however, budget constraints mean that in the implementation stage many activity programs cannot be accommodated by the Technical Regional Apparatus.Community participation in Musrembang in Nabire Regency is in the form of calculative participation, based onprofit relationship orientation, as in business contracts and taking into account economic values.Suggestion forThe Bappeda team at the Musrenbang at the District Level together with the community must classify all proposed activity programs into their funding sources. Especially those that will be financed by APBD II (Kabupaten). Next, prepare and agree on the program of activities according to the priority needs of the community.